AI-empowered Library Reading Therapy: A Study on the Path to Alleviate the Inferiority Complex of Poor Students in Western Universities (Journal of science and technology exploration, 2025)
This article focuses on the issue of inferiority complex among impoverished students in western universities, exploring how AI technology can empower library reading therapy and establish an effective psychological intervention path. Studies show that poor students in western colleges and universities are prone to have a strong sense of inferiority due to factors such as economic pressure, social environment, school education and personal cognition. Traditional reading therapy has problems such as limited resources and insufficient personalization. By constructing a four-dimensional path of "data-driven - resource construction - technology application - effect evaluation", AI technology can achieve precise identification, personalized book recommendation for reading, intelligent interactive companionship and dynamic effect evaluation, forming a systematic intervention plan. Finally, this paper puts forward relevant implementation suggestions and future prospects, providing theoretical and practical references for alleviating the inferiority complex of poor students in western colleges and universities.
Keywords: AI empowerment; Western universities; Poor students; Inferiority complex; Library reading therapy